Indicadores bibliométricos em ciência da informação: análise dos pesquisadores mais produtivos no tema estudos métricos na base Scopus - Oliveira, Ely Francina Tannuri de [UNESP]; Grácio, Maria Cláudia Cabrini [UNESP] (Escola de Ciência da Informação da UFMG, 2011)
This research aims at analyzing the indicators of impact and relevance - total of published articles, average of citations, total number of citations and index h of the most productive researchers in the Metric Studies field, within periods of the Scopus base by means of a correlation study, determining the best equation of regression of index h due to the total of citations, as well as to all other indicators under analysis. As research procedure, we used the search terms bibliometr* OR scientometr* OR infometr* OR webometr* OR informetr* OR webmemetr* OR paentometr*, obtaining 36 researchers as the most productive ones. For each indicator, the following descriptive statistics were calculated: maximum, minimum, average, standard deviation and coefficient of variation. The coefficient of correlation of Pearson was calculated and adjusted to the equation of regression of index h due to the total of citations. The equation of multiple regression was identified, from index h due to the other indicators. Concluding, we highlight the need for a matching of such indicators to broadly describe a researcher's multifaceted profile, seeing the complementarity of information provided by the indicators of productivity and impact, from distinctive nature.
Bibliometric indicators in information science: analysis of the most productive researchers about metric studies in the Scopus basis
Keywords: Estudos métricos; Indicadores bibliométricos; Produção científica; Indicadores de citação; Índice h; Metric studies; Bibliometric indicators; Scientific production; Citation indicators; Index h